Derap Lars Penopang Produksi PG Gondang Baru Pasca Nasionalisasi, 1957-1967 - Hadi, Putro Wasista (Universitas Negeri Yogyakarta, 2024)
This article discusses the Gondang Baru Sugar Factory company after it was nationalized at the end of 1957, particularly the militarization that participated and became a determining factor in the company's operations a decade later. The subject matter will discuss the various managerial measurements taken after the company was nationalized, especially when the security department was headed by an ex-military named Darmoatmodjo. In order to assist in finding sources and interpreting data, both quantitative and qualitative, the business history method is used in this research. As a result, it is understandable that militarism in PG Gondang Baru occurs subtly in reference to its basic capabilities as a security service. However, the combination of the military as a security service with the various ranks of Klaten's Pamong Praja has managed to raise productivity figures measured by both the area of concession land and the percentage of theft throughout the decade of PG Gondang Baru's management after nationalization.Keywords: Militarization, PG Gondang Baru, Nationalization.